Synthesis, Structural Elucidation and Pharmacological Applications of Cu(II) Heteroleptic Carboxylates - Shaker Ullah; Muhammad Sirajuddin; Zafran Ullah; Afifa Mushtaq; Saba Naz; Muhammad Zubair; Ali Haider; Saqib Ali; Maciej Kubicki; Tanveer A. Wani; Seema Zargar; Mehboob Ur Rehman (MDPI AG, 2023)
Six heteroleptic Cu(II) carboxylates (1-6) were prepared by reacting 2-chlorophenyl acetic acid (L1), 3-chlorophenyl acetic acid (L2), and substituted pyridine (2-cyanopyridine and 2-chlorocyanopyridine). The solid-state behavior of the complexes was described via vibrational spectroscopy (FT-IR), which revealed that the carboxylate moieties adopted different coordination modes around the Cu(II) center. A paddlewheel dinuclear structure with distorted square pyramidal geometry was elucidated from the crystal data for complexes 2 and 5 with substituted pyridine moieties at the axial positions. The presence of irreversible metal-centered oxidation reduction peaks confirms the electroactive nature of the complexes. A relatively higher binding affinity was observed for the interaction of SS-DNA with complexes 2-6 compared to L1 and L2. The findings of the DNA interaction study indicate an intercalative mode of interaction. The maximum inhibition against acetylcholinesterase enzyme was caused for complex 2 (IC50 = 2 µg/mL) compared to the standard drug Glutamine (IC50 = 2.10 µg/mL) while the maximum inhibition was found for butyrylcholinesterase enzyme by complex 4 (IC50 = 3 µg/mL) compared to the standard drug Glutamine (IC50 = 3.40 µg/mL). The findings of the enzymatic activity suggest that the under study compounds have potential for curing of Alzheimer's disease. Similarly, complexes 2 and 4 possess the maximum inhibition as revealed from the free radical scavenging activity performed against DPPH and H2O2.